Pemasaran Media Sosial Instagram Dalam Meningkatkan Citra Merek Pada PT. BAYU BUANA TRAVEL - Agustina, Susi; Burhanuddin, Radyta Achmad; Wahjono, Dani Siswardhani; Hilvania, Iche (LPPM Universitas Bina Sarana Informatika, 2025)
PT. Bayu Buana Travel is a company engaged in the field of travel agents. Marketing international tour packages owned, using social media such as Instagram (@bayubuanatravel). The use of social media as a medium for marketing or promotion can reach a wide marketing network that cannot be reached offline. So that people can see various products of PT. Bayu Buana Travel easily. This study is to determine the use of social media as a medium for marketing products at the PT. Bayu Buana Travel Travel Agent. Using the qualitative research method because this method is expected to provide a holistic understanding in expressing a reality directly. Descriptive research is research that aims to describe a situation, event, and everything related to the object, explaining how social media is used to market or promote a product and what obstacles occur when promoting through social media. Data collection using observation and interviews with key informants from PT. Bayu Buana Travel. In marketing products through social media, PT. Bayu Buana Travel spreads information with entertainment, interaction, trendiness, customization, and word of mouth (WOM). The success rate of PT. Bayu Buana Travel has been quite successful in marketing products through Instagram social media or the NADIA service (Bayu Buana Digital Travel Assistant) to ask about international tour packages or purchase plane tickets, hotels, and so on so that the sales process continues.